Noetic-spiritual dimension of personality in the process of coping with cancer related stress - Piskozub, Mirosław (Psychoonkologia, 2010)
Background : The psychological consequences of cancer touch all aspects of human life. This article presents empirical explorations, which focus on the functioning of the oncology patient in three areas: coping with stress, religiosity and the sense of meaning of life. The researches conducted so far have shown the strong influence of coping strategies on the shape of changes in psychosocial functioning of ill people. The results of research in “Psycho-Oncology” have indicated an important role of the noetic-spiritual dimension in the process of coping with cancer related stress. These scientific facts indicate the need for further exploration in this area. Aim of the study : To present research was to examine how the oncological stress changes the functioning of a patient in the scope of three variables: coping with stress, religiosity and the sense of meaning of life. Moreover it was aimed at pointing to how religiosity and the sense of meaning of life correlate with the styles of coping with stress. Material and methods : 32 patients from the Oncology Center of Warsaw (study group) and 32 persons who have never so far been diagnosed with cancer (control group) took part in this project. The following techniques: Endler and Parker’s CISS inventory for measuring styles of coping with stress, Jaworski’s Personal Religiosity Scale, Crumbaugh and Maholick’s Purpose of Life Test have been administrated to the participants. Results : The results indicate significant differences between the group of patients with cancer and the control group only in the range of coping with stress. Apart from that, personal religiosity and the sense of meaning of life correlate with preferences of coping strategies. Conclusions : The specific features of stress related with a life-threatening illness modify behaviors in related to coping with stress. Spirituality plays an important role in this area. This study assume that spirituality express by personal religiosity and the sense of meaning of life. The treatment of psychological consequences of cancer illness should take into consideration the spiritual activity of patients.